THE ROLE OF THE mTOR NUTRIENT SIGNALING PATHWAY IN CHONDROCYTE DIFFERENTIATION - Phornphutkul, Chanika (2008)
The mammalian Target of Rapamycin (mTOR) is a nutrient-sensing protein kinase that regulates numerous cellular processes. Physilogical fetal rat metatarsal explant cultures were used, to study the effect of mTOR inhibition on chondrogenesis. Insulin significantly enhanced bone growth. Rapamycin significantly diminished the growth response to insulin, selectively on hypertrophic zone. Cell proliferation (BrdU incorporation) was unaffected by rapamycin. Similar observation was noted in In vivo injection of rapamycin to E19 fetal rats. In ATDC5 chondrogenic cell line, rapamycin inhibited proteoglycan accumulation and collagen X expression. Rapamycin decreased Indian Hedgehog (Ihh) accumulation, a regulator of chondrocyte differentiation. Furthermore, addition of Ihh to culture media was able to reverse of effect of rapamycin. We conclude that modulation of mTOR signaling contributes to chondrocyte differentiation, perhaps through its ability to regulate Ihh expression. Our findings are consistent with the hypothesis that nutrients, acting through mTOR, directly influence chondrocyte differentiation and long bone growth.